Developing a sourcebook on traditional vernacular houses, construction methods, and house-building rituals of five ethnolinguistic groups in Mindanao - Cabahug, Lyndon John B. (2015)
The study aims to document the physical characteristics and design configuration of the different traditional vernacular houses as well as its construction process and house-building rituals. Mindanao is a melting pot of numerous indigenous cultures all of which are changing due to the fast pace of modernization. This change in culture is also manifested in their architecture which can contribute to the country?s heritage. In this study, one traditional vernacular house was documented from each of the five selected ethnolinguistic groups. These are the Gunu Udi of the Tboli, Gumme of the Blaan, Torogan of the Maranao, Bale of the Bagobo, and Bay of the Tausug. The following qualities were common among the five houses: (1) the structure is raised from the ground, (2) building orientation is based on the direction of slope and the East-West axis, (3) there is a central area provided for guests, (4) the interior is partitionless, and (5) the deepest space the sleeping area. The study concluded that the observable characteristics of the houses were not only based from local climatic conditions but were also influenced by a series of socio-cultural factors such as belief systems, economic status, family dynamics, and customary practices. A more thorough documentation should be done not only the houses, but all traditional vernacular structures including those belonging to other Mindanao ethnolinguistic groups. Conservation projects should also be done to protect this important heritage.